Dynamic changes of gut fungal community in horse at different health states - Lan, Yanfang; Li, Yaonan; Yu, Gang; Zhang, Zhengyi; Irshad, Irfan (Frontiers in Veterinary Science, 2022)
Accumulating surveys indicated that gut microbial changes played key roles in the progression of multiple diseases, which seriously threaten the host health. Gut microbial imbalance is closely associated with the development of diarrhea, but gut microbial composition and variability in diarrheic horses have not been well characterized. In this study, we compared gut fungal compositions and changes in healthy and diarrheic horses using amplicon sequencing. Results indicated that the alpha and beta diversities of gut fungal community in diarrheal horses changed markedly, accompanied by distinct shifts in taxonomic compositions. The types of main fungal phyla (Neocallimastigomycota, Ascomycota and Basidiomycota) in healthy and diarrheal horses were same but different in richness. However, the species and abundance of dominant fungal genera in diarrheal horses changed significantly compared with healthy horses. Results of Metastats analysis indicated that all differential fungal phyla (Blastocladiomycota, Kickxellomycota, Rozellomycota, Ascomycota, Basidiomycota, Chytridiomycota, Mortierellomycota, Neocallimastigomycota, Glomeromycota and Olpidiomycota) showed a decreasing trend during diarrhea. Moreover, a total of 175 differential fungal genera were identified for the gut fungal community between healthy and diarrheal horses, where 4 fungal genera increased observably, 171 bacterial genera reduced dramatically during diarrhea. Among these decreased bacteria, 74 fungal genera even completely disappeared from the intestine. In addition, this is the first comparative analysis of equine gut fungal community in different health states, which is beneficial to understand the important role of gut fungal community in equine health.